Multi-Omics Studies Demonstrate Toxoplasma gondii-Induced Metabolic Reprogramming of Murine Dendritic Cells - Hargrave, Kerrie E.; Woods, Stuart; Millington, Owain; Chalmers, Susan; Westrop, Gareth D.; Roberts, Craig W. (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii can actively invade almost any mammalian cell type including phagocytes. Early events in phagocytic cells such as dendritic cells are key to establishing parasite infection, but conversely play a pivotal role in initiating host immunity. It is now recognised that in addition to changes in canonical immune markers and mediators, alteration in metabolism occurs upon activation of phagocytic cells. These metabolic changes are important for supporting the developing immune response, but can affect the availability of nutrients for intracellular pathogens including T. gondii. However, the interaction of T. gondii with these cells and particularly how infection changes their metabolism has not been extensively investigated. Herein, we use a multi-omics approach comprising transcriptomics and metabolomics, validated with functional assays to better understand early events in these cells following infection. Analysis of the transcriptome of T. gondii infected bone marrow derived dendritic cells (BMDCs) revealed significant alterations in transcripts associated with cellular metabolism, activation of T cells, and inflammation mediated chemokine and cytokine signalling pathways. Multivariant analysis of metabolomic data sets acquired through non-targeted liquid chromatography mass spectroscopy (LCMS) identified metabolites associated with glycolysis, the TCA cycle, oxidative phosphorylation and arginine metabolism as major discriminants between control uninfected and T. gondii infected cells. Consistent with these observations, glucose uptake and lactate dehydrogenase activity were upregulated in T. gondii infected BMDC cultures compared with control BMDCs. Conversely, BMDC mitochondrial membrane potential was reduced in T. gondii-infected cells relative to mitochondria of control BMDCs. The changes to energy metabolism are often termed the Warburg effect. This metabolic reprogramming of cells has been suggested to be an important adaption that provides energy and precursors to facilitate phagocytosis, antigen processing and cytokine production. Other changes to BMDC metabolism are evident following T. gondii infection and include upregulation of arginine degradation concomitant with increased arginase-1 activity and ornithine and proline production. As T. gondii is an arginine auxotroph the resultant reduced cellular arginine levels are likely to curtail parasite multiplication. These results highlight the complex interplay of BMDCs and parasite metabolism within the developing immune response and the consequences for adaptive immunity and pathogen clearance.